2022
DOI: 10.1002/ece3.8547
|View full text |Cite
|
Sign up to set email alerts
|

Genetic assessment reveals inbreeding, possible hybridization, and low levels of genetic structure in a declining goose population

Abstract: The population numbers of taiga bean goose (Anser fabalis fabalis) have halved during recent decades. Since this subspecies is hunted throughout most of its range, the decline is of management concern. Knowledge of the genetic population structure and diversity is important for guiding management and conservation efforts. Genetically unique subpopulations might be hunted to extinction if not managed separately, and any inbreeding depression or lack of genetic diversity may affect the ability to adapt to changi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 124 publications
(160 reference statements)
2
8
0
Order By: Relevance
“…As pair formation among waterfowl usually takes place during winter (Rohwer & Anderson, 1988), low migratory connectivity between breeding and wintering sites should lead to genetically mixed populations. Birds marked in Finland (breeding both in Finland and Russia) showed low connectivity (Figure 3), so our results are coherent with the recent study by Honka et al (2022), who found no genetic structure among the taiga bean geese sampled in Finland. The geese wintering in Denmark showed higher migratory connectivity (Figure 3), potentially leading to genetic differentiation between the birds wintering in Denmark and Sweden, although this has not been investigated to date.…”
Section: Discussionsupporting
confidence: 92%
“…As pair formation among waterfowl usually takes place during winter (Rohwer & Anderson, 1988), low migratory connectivity between breeding and wintering sites should lead to genetically mixed populations. Birds marked in Finland (breeding both in Finland and Russia) showed low connectivity (Figure 3), so our results are coherent with the recent study by Honka et al (2022), who found no genetic structure among the taiga bean geese sampled in Finland. The geese wintering in Denmark showed higher migratory connectivity (Figure 3), potentially leading to genetic differentiation between the birds wintering in Denmark and Sweden, although this has not been investigated to date.…”
Section: Discussionsupporting
confidence: 92%
“…As pair formation among waterfowl usually takes place during winter (Rohwer & Anderson, 1988), low migratory connectivity between breeding and wintering sites should lead to genetically mixed populations. Birds marked in Finland (breeding both in Finland and Russia) showed low connectivity (Figure 3), so our results are coherent with the recent study by Honka et al, (2022), who found no genetic structure among the taiga bean geese sampled in Finland. The geese wintering in Denmark showed higher migratory connectivity (Figure 3), potentially leading to genetic differentiation between the birds wintering in Denmark and Sweden.…”
Section: Discussionsupporting
confidence: 91%
“…The offspring obtained from crossing those breeds surpassed the parental breeds in productivity and viability. In addition, they indicate the influence of interbreeding on the exterior features of poultry, affecting its meat productivity (Honka et al, 2022; Ivanov et al, 2021; Lee, 2021). A group of scientists working with Lalev et al (2014), obtained similar results.…”
Section: Discussionmentioning
confidence: 99%